The effective elastic thickness of the lithosphere in the collision zone between Arabia and Eurasia in Iran - Zamani, A.; Samiee, J.; Kirby, Jon (Pergamon, 2014)
The effective elastic thickness, Te, has been calculated in the collision zone between Arabia and Eurasia in Iran from the wavelet coherence. The wavelet coherence is calculated from Bouguer anomalies and topography data using the isotropic fan wavelet method, and gives Te values between 14.2 and 62.2 km. The lower value is found in the Central Iranian Blocks and the East Iranian Belt which are bounded by several large strike-slip faults with lithospheric origin. The higher value occurs in the east of the South Caspian Sea Basin. The resulting Te map shows positive and negative correlation with shear wave velocity and surface heat flow, respectively. A comparison between the seismogenic thickness (Ts) and Te in Iran suggests that Te > Ts. Results of the load ratio in Iran indicate that in most of the study area surface loads are much more prevalent than subsurface loads, except in the Central Iranian Blocks and NW of Iran. Intermediate to low Te values in Iran were inherited from multiple rifting and orogenic activities from Late Precambrian (~650 Ma) to present day which are not only reflected in thin and warm lithosphere but also an increasing seismicity rate.